Pendidikan Dalam Pemikiran Ibnu Khuldun Dan Kh Ahmad Dahlan (Sebagai Refleksi Sistem Pendidikan Islam Indonesia Di Era Perkembangan) - Yunia Sari, Nia (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2020)
The era of modernization is an era where developments and changes cover all aspects of human life. The development of the times seemed to continue running and make a change that is so obvious. Every human who lives in this era seems to continue to experience spontaneous changes whether consciously or unconsciously. These developments and changes permeate all aspects of life, including those in the aspect of education. Education in the modern era continues to improve, educational actors are competing to improve the quality of education according to their development, following the times, following the wishes of the people who are currently very